Water-soluble high-nuclear rare earth tungsten polyacid cluster compound as well as preparation method and application thereof
Water-soluble high-nuclear rare earth tungsten polyacid clusters were prepared by hydrothermal synthesis and applied in aqueous zinc ion batteries to form a new two-dimensional honeycomb infinitely expanded cluster base layer, solving the growth, corrosion and hydrogen evolution reaction of zinc dendrites Problem, significantly improving the service life and stability of the battery.
Patent Information
- Application Number
- CN202411682705.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-22
AI Technical Summary
In practical applications, aqueous zinc ion batteries face problems such as zinc dendrites growth, corrosion and hydrogen evolution reaction, and the development of dual-function electrolyte additives is relatively slow, resulting in insufficient additive stability.
A water-soluble high-nuclear rare earth tungsten polyacid cluster compound was prepared by hydrothermal synthesis. As an electrolyte additive, it forms a new two-dimensional honeycomb infinitely expanded cluster base layer by interacting with ZnSO4 solution, inhibiting side reactions and branches of zinc anode Crystal growth.
This water-soluble high-nuclear rare earth tungsten polyacid cluster compound significantly improves the service life of zinc ion batteries, has good stability, and improves the electrochemical performance of zinc anode by inhibiting side reactions and dendrites.
Smart Images

Figure CN119504868A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of crystal materials and electrolyte additives, and specifically relates to a water-soluble high-nuclear rare earth tungsten polyacid cluster compound and a preparation method and application thereof. Background Art
[0002] In the energy field, the development and application of lithium-ion batteries are limited due to the limited availability of lithium resources and safety issues caused by the use of flammable organic electrolytes. Aqueous zinc-ion batteries (AZIBs) are a promising alternative with low cost, high safety, a theoretical specific capacity of 820 mAh / g, and Zn 2+ However, its practical application faces problems such as zinc dendrite growth, corrosion and hydrogen evolution reaction (HER).
[0003] Therefore, researchers are committed to developing strategies to improve the performance of zinc anodes, including membrane modification, artificial protective layer construction, and electrolyte regulation. Among them, the addition of additives to the electrolyte is considered to be an effective strategy to regulate and stabilize the zinc anode. The functions of electrolyte additives can be divided into two categories: the first category involves shielding the tip effect to inhibit dendrite growth; the second category aims to inhibit side reactions such as HER. At present, some progress has been made in improving the performance of AZIBs with single-functional electrolyte additives. In comparison, the development of bifunctional electrolyte additives has been relatively slow. In addition, due to the consumption of additives during the cycle, which will lead to their insufficient stability, there is an urgent need to develop stable and efficient bifunctional electrolyte additives.
[0004] Polyoxometalates (POMs) are a class of polyoxyanions composed of early transition metals (W, Mo, V, Nb, Ta) and oxygen atoms. POMs have diverse structures and excellent chemical properties, and are widely used in catalysis, medicine, batteries and other fields. In particular, they can accommodate a large number of electrons and ions in redox reactions while maintaining structural stability. Fascinatingly, this property makes POM a potential class of highly efficient AZIBs electrolyte additives. However, research in this area is quite limited and urgently needs to be expanded, especially the study of POM as a dual-functional electrolyte additive. Summary of the invention
[0005] To solve the above problems, the present invention proposes a water-soluble high-nuclear rare earth tungsten polyacid cluster compound and a preparation method and application thereof. The preparation method of the present invention is simple, and the prepared water-soluble high-nuclear rare earth tungsten polyacid cluster compound exhibits excellent electrolyte modification performance in aqueous zinc ion batteries, greatly improves the service life of the battery, and has good stability.
[0006] The present invention adopts the following technical solutions:
[0007] A water-soluble high-nuclear rare earth tungsten polyacid cluster compound, wherein the molecular formula of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound is:
[0008] [H 2 N(CH 3 ) 2 ] 9 H 5.5 Na 8 [Nd 9 (OH) 6 (H 2 O) 6 (NO 3 )(XO 4 )(A-α-SiW 9 O 34 )(A-α-SiW 10 O 37 ) 3 ]·50H 2 O, wherein X=0.25Si+0.75W; A-α represents the configuration of the metal-oxygen cluster; the water-soluble high-nuclear rare earth tungsten polyacid cluster compound crystallizes in the triclinic system, the space group is P-1, and the crystal structure is C 3 Symmetrical three-shell structure, the innermost layer is a flat triangular NO 3 - Anion; Shell 2 consists of two parts, one of which is composed of three nine-coordinated NdO 5 (OH) 3 (H 2 O), 3 eight-coordinated NdO 6 (OH)(H 2 O) and three octa-coordinated NdO 6 (OH) 2 The cup-shaped nine nuclei {Nd 9 O 37 (OH) 6 (H 2 O) 6} cluster, and the other part is a XO with disordered distribution of Si and W 4 Tetrahedron, XO 4 Tetrahedron with three NdO 6 (OH)(H 2 O) forms a cage-like {Nd 9 O 33 (OH) 6 (H 2 O) 6 (XO 4 )} cluster; Shell 3 is composed of a {A-α-SiW 9 O 34}Tungsten polyacid clusters and three {A-α-SiW 10 O 37}It is composed of tungsten polyacid clusters.
[0009] Preferably, the unit cell parameters of the water-soluble high-nuclear rare earth tungsten polyacid cluster are: α=103.0350(10)°, β=106.7890(10)°, γ=97.0860(10)°, The calculated density is 3.347 g / cm 3 .
[0010] A method for preparing a water-soluble high-nuclear rare earth tungsten polyacid cluster compound, the specific preparation process is: weighing the precursor Na 10 [A-α-SiW 9 O 34 ]·18H 2 O, neodymium nitrate hexahydrate, nickel hydroxide, and dimethylamine hydrochloride are dissolved in water, and then the pH of the mixed solution is adjusted to 10 with sodium hydroxide, and then fully stirred, and then transferred into a polytetrafluoroethylene reactor, and placed in an oven for hydrothermal reaction, the solution after the hydrothermal reaction is filtered, and the filtrate is slowly volatilized at room temperature for one week, and the product obtained after volatilization is collected and washed to obtain purple block crystals, that is, a water-soluble high-nuclear rare earth tungsten polyacid cluster compound is obtained; the precursor Na 10 [A-α-SiW 9 O 34 ]·18H 2 O, neodymium nitrate hexahydrate, nickel hydroxide, dimethylamine hydrochloride and water are added in a molar ratio of 0.095:0.19:0.32:0.93:222.22; the temperature of the hydrothermal reaction is 140° C., and the reaction time is 5 days.
[0011] An application of a water-soluble high-nuclear rare earth tungsten polyacid cluster compound, wherein the water-soluble high-nuclear rare earth tungsten polyacid cluster compound is used as an electrolyte additive in the field of aqueous zinc ion batteries; the water-soluble high-nuclear rare earth tungsten polyacid cluster compound is dissolved in ZnSO 4 In solution, the cluster anions and Zn 2+ The interactions between them induce in-situ connections between clusters, generating a new two-dimensional cellular base layer of infinitely extended clusters.
[0012] After adopting the above technical scheme, the present invention has the following advantages compared with the background technology: the preparation method of the present invention is simple, and a high-yield pure water-soluble high-nuclear rare earth tungsten polyacid cluster compound can be obtained by a hydrothermal synthesis method combined with a volatilization method. The water-soluble high-nuclear rare earth tungsten polyacid cluster compound is a novel high-nuclear tungsten polyacid cluster compound formed by substitution of a nine-nuclear neodymium cluster. The prepared water-soluble high-nuclear rare earth tungsten polyacid cluster compound exhibits a relatively excellent electrolyte additive effect in aqueous zinc ion batteries, and can form a protective layer on the zinc anode, effectively inhibiting the side reactions on the zinc anode, and inhibiting the growth of zinc dendrites, promoting Zn 2+ The uniform deposition of ions on the anode surface greatly increases the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a crystal photo of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound, which is the product of Example 1 of the present invention;
[0014] Figure 2 This is a structural diagram of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound, which is the product of Example 1 of the present invention;
[0015] Figure 3 The X-ray powder diffraction (XRD) diagram of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1 of the present invention;
[0016] Figure 4 The water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1 of the present invention is respectively prepared in aqueous solution and ZnSO 4 UV-vis graph of liquid in solution;
[0017] Figure 5 The water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1 of the present invention is prepared in ZnSO 4 The structural diagram of the infinitely extended cluster base layer transformed in situ into a new 2D honeycomb in solution;
[0018] Figure 6 The water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1 of the present invention is prepared in ZnSO 4 XRD pattern of the infinitely extended cluster base layer transformed in situ into a new 2D honeycomb in solution;
[0019] Figure 7 The water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1 of the present invention is prepared in ZnSO 4 Time-resolved liquid UV-vis images in solution;
[0020] Figure 8 The water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1 of the present invention is added at different amounts at 1 mA cm -2 、1mAh cm -2Long-term cycling performance diagram of Zn||Zn symmetric battery when ;
[0021] Fig. 9 The water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1 of the present invention is subjected to different addition amounts at 5 mA cm -2 、1mAh cm -2 Long-term cycling performance of Zn||Zn symmetric battery at high current density;
[0022] Fig.10 This is a time-voltage-rate performance diagram of the product of Example 1 of the present invention using ZSPE-2 and ZSPE-0 electrolytes;
[0023] Fig.11 The XRD diagram of the zinc foil using ZSPE-2 and ZSPE-0 electrolytes and the XRD diagram of the zinc foil converted into a new 2D honeycomb infinitely extended cluster base layer are shown in Example 1 of the present invention;
[0024] Fig.12 The UV-vis graphs of zinc foil and bare zinc using ZSPE-2 and ZSPE-0 electrolytes as the product of Example 1 of the present invention;
[0025] Fig.13 The Tafel curve diagram of the product of Example 1 of the present invention when using ZSPE-2 and ZSPE-0 electrolytes;
[0026] Fig.14 The polarization curves of the zinc electrode when the product of Example 1 of the present invention uses ZSPE-2 and ZSPE-0 electrolytes;
[0027] Fig.15 The product of Example 1 of the present invention uses ZSPE-2 and ZSPE-0 electrolytes at 1 mA cm -2 、1mAh cm -2 XRD patterns of zinc foil and bare zinc after cycling at different current densities;
[0028] Fig.16 This is a dendrite growth diagram of the zinc foil using ZSPE-2 electrolyte observed under an in-situ metallographic microscope;
[0029] Fig.17 This is a dendrite growth diagram of the zinc foil using ZSPE-0 electrolyte observed under an in-situ metallographic microscope;
[0030] Fig.18 This is a characterization diagram of the product of Example 1 of the present invention measured by chronoamperometry using ZSPE-2 and ZSPE-0 electrolytes;
[0031] Fig.19This is a SEM image of the zinc anode surface after the product of Example 1 of the present invention was cycled 100 times using ZSPE-2 and ZSPE-0 electrolytes;
[0032] Fig. 20 The nucleation overpotential diagram of the product of Example 1 of the present invention using ZSPE-2 and ZSPE-0 electrolytes;
[0033] Fig.21 The Zn content of the product of Example 1 of the present invention when different amounts of rare high-nuclear rare earth tungsten polyacid clusters with solubility and water stability are added as electrolyte 2+ Ion transfer number diagram;
[0034] Fig. 22 The Arrhenius curve and activation energy diagram of the product of Example 1 of the present invention using ZSPE-2 and ZSPE-0 electrolytes. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0036] See also Figures 1 to 22 .
[0037] Example 1
[0038] [H 2 N(CH 3 ) 2 ] 9 H 5.5 Na 8 [Nd 9 (OH) 6 (H 2 O) 6 (NO 3 )(XO 4 )(A-α-SiW 9 O 34 )(A-α-SiW 10 O 37 ) 3 ]·50H 2 O (abbreviated as [H 2 N(CH 3 ) 2 ] 9 H 5.5 Na 8 [1a], X = 0.25Si + 0.75W) Water-soluble high-nuclear rare earth tungsten polyacid clusters
[0039] According to the molar ratio of 0.095:0.19:0.32:0.93, weigh the precursor Na 10 [A-α-SiW 9 O 34 ]·18H 2 O, neodymium nitrate hexahydrate, nickel hydroxide, and dimethylamine hydrochloride were added to 4 mL of water and mixed evenly. The pH of the mixed solution was adjusted to 10 with sodium hydroxide. After stirring for 1.5 hours, the obtained mixture was charged into a 23 mL polytetrafluoroethylene reactor and placed in an oven for hydrothermal reaction. After reacting at 140° C. for 5 days, the mixture was cooled to room temperature. The reaction solution was filtered, and the filtrate was slowly evaporated at room temperature for one week. The product obtained after the volatilization was collected and washed to obtain a water-soluble high-nuclear rare earth tungsten polyacid cluster compound, that is, the product of Example 1 is [H 2 N(CH 3 ) 2 ] 9 H 5.5 Na 8 [Nd 9 (OH) 6 (H 2 O) 6 (NO 3 )(XO 4 )(A-α-SiW 9 O 34 )(A-α-SiW 10 O 37 ) 3 ]·50H 2 O(X=0.25Si+0.75W).
[0040] Example 2
[0041] Example 1 Detection of the water-soluble high-nuclear rare earth tungsten polyacid cluster obtained
[0042] Take a crystal photo of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1, as shown in Figure 1 shown.
[0043] The sample of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1 was characterized by X-ray single crystal diffraction. The results are as follows: Figure 2 As shown. The crystal belongs to the P-1 space group, and its unit cell parameters are: α=103.0350(10)°, β=106.7890(10)°, γ=97.0860(10)°,
[0044] The sample structure of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound of Example 1 was analyzed by SHELX-2018 / 3, and the crystallographic parameters of the compound are shown in Table 1;
[0045] Table 1: Crystallographic parameters of water-soluble high-nuclear rare earth tungsten polyacid clusters
[0046]
[0047] a R 1 =Σ||Fo|-|Fc|| / Σ|Fo|, b wxya 2 =[Σw(Fo 2 -Fc 2 ) 2 / w(Fo) 2 ] 1 / 2 ,w=1 / [σ 2 (Fo 2 )+(0.1035P) 2 +2714.6177P], where P=(F 2 +2Fc 2 ) / 3.
[0049] Example 1 The product of water-soluble high-nuclear rare earth tungsten polyacid cluster was determined by X-ray powder diffraction (XRD). Figure 3 shown.
[0050] Example 1 Product Water-soluble high-nuclear rare earth tungsten polyacid clusters were prepared in aqueous solution and ZnSO 4 Liquid UV-vis in solution, such as Figure 4 shown.
[0051] Example 1 Product Water-soluble high-nuclear rare earth tungsten polyacid clusters in ZnSO 4 The structure of the infinitely extended cluster base layer in situ transformed into a new 2D honeycomb in the solution, such as Figure 5 shown.
[0052] Example 1 Product Water-soluble high-nuclear rare earth tungsten polyacid clusters in ZnSO 4 XRD determination of the infinitely extended cluster base layer in situ transformed into a new 2D honeycomb in solution, such as Figure 6 shown.
[0053] Example 1 Product Water-soluble high-nuclear rare earth tungsten polyacid clusters in ZnSO 4 Time-resolved liquid UV-vis images in solution, such as Figure 7 As shown, it indicates that in ZnSO 4 Stability in solution. Example 1 The product was in ZnSO 4Interesting structural transformation characteristics in solution and the transformed structure in ZnSO 4 The structural stability in solution makes the product of Example 1 a ZnSO 4 A potential new excellent additive for electrolytes.
[0054] 1 mL of 1.0 M ZnSO 4 The solution was mixed with 0, 10, 20 and 30 mg of the product of Example 1, respectively labeled as ZSPE-0, ZSPE-1, ZSPE-2 and ZSPE-3, to prepare a series of electrolytes. Figure 8 As shown, at 1 mA cm -2 and 1mAh cm -2 Under the same conditions, the ZSPE-0 cell exhibited a gradually increasing hysteresis accompanied by a significant voltage fluctuation within 128 h (from 50 mV to 100 mV). In sharp contrast, the ZSPE-2 cell exhibited a much more stable voltage profile over more than 2000 h (from only 74 mV to 71 mV), which lasted several dozen times longer than the cell with ZSPE-0. -2 At high current density, the ZSPE-2 battery can maintain a cycle time of more than 580 hours (e.g. Fig. 9 As shown in Figure 2, the battery life is more than 20 times longer than that of the battery with ZSPE-0 (27 hours). In addition, rate performance is an important criterion for evaluating battery performance. Fig.10 As shown, even at 10mA cm -2 At a high current density, the hysteresis voltage of the ZSPE-2 battery is 214 mV, which is 136 mV lower than that of the ZSPE-0 battery, indicating that the ZSPE-2 battery exhibits the fastest reaction kinetics.
[0055] In order to study the key role of the product of Example 1 in the zinc stripping / plating process, the product crystallized from the electrolyte ZSPE-2 after 200 h of battery cycling was first characterized using X-ray single crystal diffraction. The results show that the product of Example 1 has a significant influence on the ZnSO 4 The new 2D honeycomb infinitely extended cluster-based structure was in situ converted into a new 2D honeycomb infinitely extended cluster-based structure in the solution, indicating that the product of Example 1 was reacted with ZnSO 4 The new 2D honeycomb infinitely extended cluster-based structure formed by the electrolyte reaction maintained structural stability during the entire battery cycle. Subsequently, the zinc electrode after charge and discharge cycles was characterized by XRD and UV-vis. The results showed that the zinc electrode cycled in ZSPE-2 showed XRD signals corresponding to the new 2D honeycomb infinitely extended cluster-based structure (such as Fig.11UV-visible spectra show that the O→W charge transfer of the new 2D honeycomb infinitely extended cluster-based structure has a characteristic peak at about 260nm (as shown in Figure 2). Fig.12 The existence of the new 2D honeycomb infinitely extended cluster-based structure was further confirmed. These findings indicate that the new 2D honeycomb infinitely extended cluster-based structure not only exists stably in the electrolyte, but also deposits on the surface of the zinc electrode to form a protective layer.
[0056] Experiments show that in 1 mL of 1.0 M ZnSO 4 After adding 20 mg of the product of Example 1 into the electrolyte, the pH value of the electrolyte increased from 4.9 to 5.9. During the charge and discharge cycle, AZIBs will inevitably 4 Side reactions such as HER occur on the zinc foil in the electrolyte, causing corrosion of the zinc foil. 4 The pH value of the electrolyte can inhibit HER. To this end, Tafel and polarization curve tests were conducted to examine the effect of the formation of the new 2D honeycomb infinitely extended cluster-based structure on the corrosion of the zinc electrode. The Tafel curve test showed that the corrosion current density (j c ) is 0.828 mA cm -2 , which is much lower than the corrosion current density in ZSPE-0 (1.206 mA cm -2 )(like Fig.13 Polarization curve (as shown). Fig.14 The results show that the hydrogen evolution current density of the zinc electrode in ZSPE-2 is significantly lower than that in ZSPE-0. The results indicate that the formation of a stable 2D honeycomb infinitely extended cluster-based structure and the subsequent increase in electrolyte pH can effectively inhibit the corrosion of HER and the generation of byproducts, thus having a positive impact on the battery life.
[0057] Afterwards, various characterization methods were used to explore what role the protective layer plays on the zinc electrode. -2 After 100 cycles (200 hours) of current density, the zinc foil was subjected to XRD test (e.g. Fig.15 As shown). It can be seen that (002) Zn The crystal face has the lowest surface energy, which is conducive to the formation of crystal nuclei. According to the Wulff structural principle, it grows into a metal crystal with a thermodynamic equilibrium structure (101). Zn The crystal face is mainly conducive to the formation of dendrites. Therefore, the XRD peak intensity ratio (I 002 / I 101 ) can be used to evaluate the ratio of zinc dendrites. The ratio of ZSPE-2 is 1.1, which is higher than that of bare zinc (0.49) and ZSPE-0 (0.46), indicating that the protective layer can induce dendrite-free zinc deposition.
[0058] Next, in situ optical microscopy was used to monitor the Zn 2+ At 5 mA cm -2 The case of sedimentation for 30 minutes. Fig.16 As shown in the figure, after 30 minutes, the zinc anode morphology of ZSPE-2 remained flat and smooth, zinc deposition was uniform, and no dendrite growth was observed. In sharp contrast, obvious zinc dendrites appeared on the surface of the zinc anode of ZSPE-0 after only 10 minutes of deposition (e.g. Fig.17 shown).
[0059] Then, chronoamperometric tests were performed to estimate the Zn 2+ Ion diffusion processes such as Fig.18 As shown. The ZSPE-0 cell exhibited a two-dimensional (2D) diffusion process that lasted up to 300 seconds. In contrast, the ZSPE-2 cell exhibited a stable three-dimensional (3D) diffusion process after a short 2D diffusion process lasting 10 seconds. Consistent 3D diffusion was observed in the ZSPE-2 cell, implying a uniform nucleation process on the Zn anode. To confirm uniform Zn deposition, the morphological evolution of the Zn anode after 100 cycles at different current densities was evaluated by scanning electron microscopy (SEM) images (see Figure 2). Fig.19 As shown, ZSPE-2 is Fig.19 In the above figure, ZSPE-0 is Fig.19 The surface of the Zn foil in ZSPE-2 is dense and uniform without protrusions, while the surface of the Zn foil in ZSPE-0 is irregular and has dendrite growth. These results indicate that the protective layer can guide uniform Zn deposition and reduce irregularities and dendrite growth.
[0060] In addition to the above characterization methods, the deposition mechanism and process in AZIBs under different electrolytes were also investigated. It was shown that a lower nucleation overpotential (ηn) can reduce the driving force of the zinc electrochemical deposition (EDZ) process, thereby promoting favorable zinc deposition kinetics as indicated by the capacity-voltage curves (e.g. Fig. 20 As shown in Figure 2, at a current density of 1 mA cm -2 When , the ηn of EDZ in the ZSPE-2 battery is 63 mV, which is lower than the ηn (76 mV) of the ZSPE-0 battery, indicating that adding the product of Example 1 to the electrolyte may enhance the deposition behavior of zinc.
[0061] In addition, Zn 2+ The slow migration kinetics in AZIBs poses a challenge to the development of AZIBs and seriously affects their service life. 2+ The transfer number is 0.75, while the Zn 2+ The number of transfers is only 0.24 (e.g. Fig.21As shown). It can be seen that adding the product of Example 1 to the electrolyte can effectively accelerate the 2+ migration, while hindering SO 4 2- The Ea value of the ZSPE-2 cell is 63.9 kJ / mol (e.g. Fig. 22 The Ea value of the ZSPE-0 battery (69.6 kJ / mol) is lower than that of the ZSPE-0 battery, indicating that adding the product of Example 1 to the electrolyte is beneficial to the Zn 2+ transfer, improving the EDZ reaction kinetics.
[0062] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A water-soluble high-nuclear rare earth tungsten polyacid cluster compound, characterized in that: The molecular formula of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound is: [H2N(CH3)2]9H 5.5 Na8[Nd9(OH)6(H2O)6(NO3)(XO4)(A-α-SiW9O 34 )(A-α-SiW 10 O 37 )3]·50H2O, wherein X=0.25Si+0.75W; A-α represents the configuration of the metal-oxygen cluster; the water-soluble high-nuclear rare earth tungsten polyacid cluster compound crystallizes in the triclinic system, the space group is P-1, and the crystal structure is a three-shell structure with C3 symmetry, the innermost layer is a planar triangular NO 3- Anion; Shell 2 consists of two parts, one of which is a cup-shaped nine-nuclear {Nd9O 37 The other part is a XO4 tetrahedron with disordered Si and W distribution. The XO4 tetrahedron and three NdO6(OH)(H2O) form a cage-like {Nd9O 33 (OH)6(H2O)6(XO4)} cluster; Shell 3 is composed of a {A-α-SiW9O 34 }Tungsten polyacid clusters and three {A-α-SiW 10 O 37 }It is composed of tungsten polyacid clusters.
2. A water-soluble high-nuclear rare earth tungsten polyacid cluster compound according to claim 1, characterized in that: The unit cell parameters of the water-soluble high-nuclear rare earth tungsten polyacid cluster are: α=103.0350(10)°, β=106.7890(10)°, γ=97.0860(10)°, The calculated density is 3.347 g / cm 3 .
3. A method for preparing a water-soluble high-nuclear rare earth tungsten polyacid cluster compound according to any one of claims 1 to 2, characterized in that: The specific preparation process is as follows: weigh the precursor Na 10 [A-α-SiW9O 34 ]·18H2O, neodymium nitrate hexahydrate, nickel hydroxide, and dimethylamine hydrochloride are dissolved in water, and then the pH of the mixed solution is adjusted to 10 with sodium hydroxide, and then fully stirred, and then transferred into a polytetrafluoroethylene reactor, and placed in an oven for hydrothermal reaction, the solution after the hydrothermal reaction is filtered, and the filtrate is slowly volatilized at room temperature for one week, and the product obtained after volatilization is collected and washed to obtain purple block crystals, that is, a water-soluble high-nuclear rare earth tungsten polyacid cluster compound is obtained; the precursor Na 10 [A-α-SiW9O 34 ]·The molar ratio of 18H2O, neodymium nitrate hexahydrate, nickel hydroxide, dimethylamine hydrochloride and water added is 0.095:0.19:0.32:0.93:222.22; the temperature of the hydrothermal reaction is 140°C and the reaction time is 5 days.
4. An application of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound according to any one of claims 1 to 2, characterized in that: The water-soluble high-nuclear rare earth tungsten polyacid cluster compound is used as an electrolyte additive in the field of aqueous zinc ion batteries; When the water-soluble high-nuclear rare earth tungsten polyacid cluster compound is dissolved in a ZnSO4 solution, the cluster anions of the water-soluble high-nuclear rare earth tungsten polyacid cluster compound and the Zn 2+ The interactions between them induce in-situ connections between clusters, generating a new two-dimensional cellular base layer of infinitely extended clusters.
Citation Information
Patent Citations
Ta / W mixed polyoxometallate and preparation method and application thereof
CN110752344A
Preparation method of ion compound and supramolecular skeleton assembly, artificial solid electrolyte interface phase and zinc metal anode
CN117747739A